Seismic Performance of Midstory Isolated Structures under Near-Field Pulse-Like Ground Motion and Limiting Deformation of Isolation Layers - Guiyun Yan; Fuquan Chen (Shock and Vibration)
Excessive deformation of the isolation layer in midstory isolated structures may occur under strong near-field pulse-like ground motion, which would result in the overturning collapse of the superstructure. The objective of the present research is to limit excessive deformation of the isolation layer and to reduce nonlinear response of midstory isolated structures. To this end, a protective system is presented to limit deformation of the isolation layer by soft pounding. Based on the Kelvin pounding model, a mechanical model is put forward for this protective system. In addition, a new method has been proposed that synthesizes artificial near-field pulse-like ground motion by combining the real near-field nonpulse ground motion with simple equivalent pulses. Also, the impact of artificial near-field pulse-like ground motion on the nonlinear response of midstory isolated structures and the deformation of the isolation layer has been investigated. The effectiveness of the midstory isolation with the protective system has been validated. The results show that the maximum deformation of the isolation layer significantly exceeds the allowable deformation of lead-rubber bearings when subjected to near-field pulse-like ground motion, and it causes the lead-rubber bearings destruction. The proposed protective system is effective in restricting the excessive deformation of the isolation layer and reducing nonlinear responses of the isolated structure, preventing collapse of the superstructure.